Is there any more room on the Ark? An analysis of space allocation in four mammalian taxa. Issue 1 (31st December 2018) - McCann, Colleen; Powell, David M.
Abstract : Zoos select species for exhibition to meet goals of recreation, education, research, and conservation. However, many zoo populations are not sustainable and institutional collection plans (ICPs) come under criticism for their lack of conservation importance. We explore the species selection process with two main questions. First, are zoos doing all they can with their available space to maintain sustainable populations? And second, are the species recommended for management in Regional Collection Plans (RCPs) important for conservation? To answer the former, we assessed how much space is allocated to recommended species versus non‐recommended species in four mammalian taxa in ICPs of 36 zoos and whether species occur in populations that are minimally robust ( n  = 100) or robust ( n  > 250) for meeting viability goals. To examine whether RCPs recommend species of conservation concern we assessed the number of species and individuals occupying available space and their IUCN category of threat. Across taxa, zoos largely incorporate recommended species into their ICPs, but very few species populations occur in sizes we consider minimally robust or robust. For Old World monkeys and antelopes, the majority of species recommended are of lower IUCN status. These results illustrate that while there is good adherence to RCPs, it could be improved and different approaches will have to be employed to reach sustainable population sizes for the recommended species. We argue that the conservation relevance of zoo populations lies not only in threat status but may be impacted by other characteristics, for example their flagship character.